Penser l'immigration maghrébine avec l'histoire coloniale - Maïlys Kydjian (Les Cahiers de Framespa)
From interviews made with the protagonists of the history of the colonization of Algeria and their descendants in Midi-Pyrenees, we put in relation this history and that of the immigration, by questioning the categories which ensue from it: the « Harki », the « Pied-Noir » and the « Algerian ». Considering colonial history, it is the concepts of territory and citizenships, eminently connected to that of migration, that are questioned to understand in what ways the history of the colonial period and that of the Algerian war for independence influence our way of considering immigration. Finally the semantic shifts associating the figures of « the immigrant », « the North African » and « the Algerian » are highlighted.